PENGARUH BRAND AWARENESS DAN BRANG IMAGE TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND ATTACHMENT SEBAGAI VARIABEL MEDIASI (Survei pada Konsumen Klinik Kecantikan Ella Skin Care Solo) - Novita Mutiyara Sani; Retno Susanti; Dorothea Ririn Indriastuti (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of brand awareness and brand image on purchasing decision wit brand attachments as a mediating variable in beauty clinic consumers ella skin care solo. The population in this study were Ella skin care solo beauty clinic consumers whose numbers were not yet known. Sampling technique uses accidental sampling. The sample is 85 respondents. This study uses quantitative analysis techniques (validity test, reliability test, multicollinearity test, autocorrelation test, heteroscedasticity test,normality test, multiple regression analysis, coefficient of determination, significance test (t test dan F test) and path analysis. The results of the study show that brand awareness and brand image have a significant effect on brand attachment. Brand awareness and brand attachment have a significant effect on purchasing decisions. Brand image does not have a significant on purchasing decision. Brand attachment mediates the influence of brand image on purchasing decision. Brand attachment does not mediate the influence of brand awareness on the decision to remove.